Proliferation and differentiation of primary bovine myoblasts using Chlorella vulgaris extract for sustainable production of cultured meat. (3rd February 2022) - Okamoto, Yuta; Haraguchi, Yuji; Yoshida, Azumi; Takahashi, Hironobu; Yamanaka, Kumiko; Sawamura, Naoya; Asahi, Toru; Shimizu, Tatsuya
Abstract: Recently, cultured meat obtained from livestock‐derived cells is being considered as a sustainable food source that reduces the use of natural resources. This study aimed to show that nutrients extracted from Chlorella vulgaris were beneficial in the culture of primary bovine myoblasts (PBMs), a major cell source for cultured meat production. Nutrients (glucose, amino acids, and vitamins) present in the animal‐cell culture media were effectively recovered from C. vulgaris using acid hydrolysis treatment. On culture in nutrient‐free inorganic salt solution, cell death was induced in most PBMs after 6 days of cultivation. However, the addition of C. vulgaris extract (CVE) significantly improved PBM viability, which was comparable to the viability in conventional culture medium (Dulbecco's modified Eagle's medium). Furthermore, by adding horse serum to induce differentiation, the formation of myotubes was confirmed when CVE were used. Together, the results showed that CVE could be used as an alternative to the conventional culture medium for PBMs. These findings will not only lower the environmental risks associated with the establishment of this eco‐friendly cell culture system, but also highlight microalgae as a potent nutrient source that can replace conventional grain‐dependent nutrient sources.